2007
DOI: 10.1086/512600
|View full text |Cite
|
Sign up to set email alerts
|

Structured Red Giant Winds with Magnetized Hot Bubbles and the Corona/Cool Wind Dividing Line

Abstract: By performing MHD simulations, we investigate the mass loss of intermediate-and low-mass stars from MS to RGB phases. Alfvén waves, which are excited by the surface convections, travel outwardly and dissipate by nonlinear processes to accelerate and heat the stellar winds. We dynamically treat these processes in open magnetic field regions from the photospheres to '25 stellar radii. When the stars evolve to slightly blueward positions of the dividing line (Linsky & Haisch), the steady hot corona with temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
121
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 63 publications
2
121
0
Order By: Relevance
“…On the other hand, the spectropolarimetric observations of Aurière et al (2010) detected no signature of magnetic fields in Aldebaran, implying that the surface-averaged field strength is much smaller than the 1 G in the model. An extension of the MHD simulations of Suzuki (2007) with weaker magnetic fields and weakly ionized plasma, as well as the inclusion of the MOLsphere component in the model of Airapetian et al (2010) would be crucial for comparison with the observed data. McMurry & Jordan (2000) propose an alternative scenario, in which the hot chromospheric gas is associated to acoustic shocks.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the spectropolarimetric observations of Aurière et al (2010) detected no signature of magnetic fields in Aldebaran, implying that the surface-averaged field strength is much smaller than the 1 G in the model. An extension of the MHD simulations of Suzuki (2007) with weaker magnetic fields and weakly ionized plasma, as well as the inclusion of the MOLsphere component in the model of Airapetian et al (2010) would be crucial for comparison with the observed data. McMurry & Jordan (2000) propose an alternative scenario, in which the hot chromospheric gas is associated to acoustic shocks.…”
Section: Discussionmentioning
confidence: 99%
“…Cranmer 2009) and stellar (e.g. Charbonneau & MacGregor 1995;Suzuki 2007) winds and coronal heating (e.g. Ofman 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They may be related to large convective cells predicted to be present in cool luminous stars (Schwarzschild 1975;Freytag et al 2002) or alternatively to thermal instability taking place in the outer atmosphere. For example, the magnetohydrodynamical simulation of Suzuki (2007) for red giant branch (RGB) stars, which are much less luminous than RSGs, shows that thermal instability leads to "structured" stellar winds with many bubbles of hot gas (∼10 5 K) embedded in cool winds (∼1−5 × 10 3 K). For cooler RSGs, the formation of molecules may also promote such thermal instability, and in particular, CO is an important coolant in the atmosphere of late-type stars (Cuntz & Muchmore 1994).…”
Section: Introductionmentioning
confidence: 99%